Sulfur isotopes quantify the impact of anthropogenic activities on industrial-era Arctic sulfate in a Greenland ice core - Ursula A Jongebloed; Andrew J Schauer; Shohei Hattori; Jihong Cole-Dai; Carleigh G Larrick; Sara Salimi; Shana R Edouard; Lei Geng; Becky Alexander (Environmental Research Letters, 2023)
Anthropogenic sulfate aerosols are estimated to have offset 60% of greenhouse-gas-induced warming in the Arctic, a region warming four times faster than the rest of the world. However, sulfate radiative forcing estimates remain uncertain because the relative contributions from anthropogenic versus natural sources to total sulfate aerosols are unknown. Here we measure sulfur isotopes of sulfate in a Summit, Greenland ice core from 1850 to 2006 CE to quantify the contribution of anthropogenic sulfur emissions to ice core sulfate. We use a Keeling plot to determine the anthropogenic sulfur isotopic signature (δ ^34 S _anthro = +2.9 ± 0.3 ‰), and compare this result to a compilation of sulfur isotope measurements of oil and coal. Using δ ^34 S _anthro , we quantify anthropogenic sulfate concentration separated from natural sulfate. Anthropogenic sulfate concentration increases to 67 ± 7% of non-sea-salt sulfate (65.1 ± 20.2 µ g kg ^−1 ) during peak anthropogenic emissions from 1960 to 1990 and decreases to 45 ± 11% of non-sea-salt sulfate (25.4 ± 12.8 µ g kg ^−1 ) from 1996 to 2006. These observations provide the first long-term record of anthropogenic sulfate distinguished from natural sources (e.g. volcanoes, dimethyl sulfide), and can be used to evaluate model characterization of anthropogenic sulfate aerosol fraction and radiative forcing over the industrial era.